Kompetensi Siswa Terhadap Pembelajaran Instalasi Listrik Kelas XI TITL SMK Cendekia Batujajar - Dina Hardianti; Kamila Salma Ningtias; Lily Octaviani; Taufik Ismail Shobirin; Wahyu Ramdani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This paper discusses the research conducted related to learning about electrical installation at Cendekia Batujajar Vocational School. This study aims to increase competency and determine students' knowledge and understanding of learning about electrical installation at Cendekia Batujajar Vocational School, where this learning has a percentage of 56,6% where students are less interested in the selection. The research was conducted through a direct, active and interactive learning approach. This development procedure is carried out by applying a project-based learning development model. Electrical installation learning is related to understanding, installing, operating, and maintaining electrical installations. Knowledge and understanding of students after this research has a good response where there is an increase shown by the percentage of 72% which means quite good.Â